Effect of magnetic muscles stimulation on the biomechanical structure of sambo throws - Popov, G.I.; Sviridov, B.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to improvement of the biomechanical structure of throws in sambo when using magnetic stimulation of the quadriceps muscles of the thighs of athletes in the isokinetic mode of their functioning. Methods and structure of the study. Four wrestlers of the 1st category, three candidates for the master of sports and three masters of sports participated in the experiment. The average age of the subjects was 18.5±3.5 years. All subjects are students of Russian State University of Physical Education, Sports, Youth and Tourism, active athletes. The methodology of the experiment was as follows: against the background of planned training work, the subjects were exposed to magnetic stimulation in the mode for 10 consecutive days. Stimulation was given when performing an oscillatory movement of the lower leg in the isokinetic mode on Biodex. Results and conclusions. The conducted cycle of magnetic stimulation led to a predominant shift of the characteristic frequencies of the spectrum of the integrated electromyogram to a higher frequency part of the spectrum. An analysis of the phase composition of throws in wrestlers subjected to magnetic stimulation showed that after the experiment, the time of the second phase decreased and the total time for performing each of the throws decreased. Quantitative values of the parameters of dynamograms, such as the maximum repulsion force, the rate of increase in force during the vertical jump showed a significant increase in their values (p<0.05 and p<0.01) in wrestlers who underwent a course of magnetic stimula- tion. They also showed a significant (p<0.05) decrease in the time to reach the maximum force.